Curie´s Principle and Indeterminism - Rolleri, José Luis (ENDOXA, 2020)
Curiés principle expresses an invariant connectiobn between symmetry of causes and symmetry of effects in deterministic systems. Here a probabilistic version of such principle is proposed and proved for indeterministic systems. In contrast with Curie´s principle, our probabilistic version involves the invariance of the probabilities that laws assign to physically possible final states of random processes under symmetry transformations, although with exceptions when a phenomenon breaks the symmetry in question.